2018
DOI: 10.1002/14651858.cd006897.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Different durations of corticosteroid therapy for exacerbations of chronic obstructive pulmonary disease

Abstract: Information from a new large study has increased our confidence that five days of oral corticosteroids is likely to be sufficient for treatment of adults with acute exacerbations of COPD, and this review suggests that the likelihood is low that shorter courses of systemic corticosteroids (of around five days) lead to worse outcomes than are seen with longer (10 to 14 days) courses. We graded most available evidence as moderate in quality because of imprecision; further research may have an important impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 71 publications
2
62
0
6
Order By: Relevance
“…We reported interesting results for association between corticosteroids and early readmission in AECOPD patients, by showing that corticosteroid use for more than 5 days was associated with an increased risk of rehospitalisation. Our results correspond to recent meta-analysis results and recommendations that long-term corticosteroid use during hospitalisation has no benefit compared with short-term use [27]. This is the first study to report on the status and related predictors of AECOPD rehospitalisation using a nationwide healthcare database in Korea.…”
Section: Discussionsupporting
confidence: 89%
“…We reported interesting results for association between corticosteroids and early readmission in AECOPD patients, by showing that corticosteroid use for more than 5 days was associated with an increased risk of rehospitalisation. Our results correspond to recent meta-analysis results and recommendations that long-term corticosteroid use during hospitalisation has no benefit compared with short-term use [27]. This is the first study to report on the status and related predictors of AECOPD rehospitalisation using a nationwide healthcare database in Korea.…”
Section: Discussionsupporting
confidence: 89%
“…The Reduction in the Use of Corticosteroids in Exacerbated COPD (REDUCE) trial showed that a 5‐day course of oral corticosteroids was not inferior to a 14‐day course in terms of exacerbation recurrence but with a shorter length of hospital stay . A Cochrane review suggested that a short course, 3 to 7 days, of systemic corticosteroids does not lead to increase in treatment failure or risk of relapse of AECOPD. Data regarding the use of systemic corticosteroids are limited in the Asia‐Pacific region.…”
Section: Management Of Acute Exacerbations Of Copdmentioning
confidence: 99%
“…50 mg sollten nicht überschritten werden. Eine neuere Untersuchung belegt zusammen mit einer Metaanalyse die Wirksamkeit bei einer Therapiedauer von 5 Tagen [372,373]. Allerdings muss individuell entschieden werden, ob diese Therapiedauer im Einzelfall ausreichend ist.…”
Section: Definitionunclassified